Lithium-supplemented positive electrode slurry and preparation method thereof, positive electrode sheet, and lithium-ion battery

By using a silane additives and weak acid additives in the lithium node pole slurry, the problem of excessive alkali surface residual alkali on the orthodox lithium supplement agent is solved, and the battery life extension and performance improvement are achieved.

CN118676375BActive Publication Date: 2025-01-24JIANGSU TIANHE ENERGY STORAGE CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411155898.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2025-01-24
Estimated Expiration
2044-08-22

AI Technical Summary

Technical Problem

The residual alkali content on the surface of the existing positive electrode lithium supplement agent is too high, resulting in a degradation of battery performance and affecting cycle life and rate performance.

Method used

Add silicane additives and weak acid additives to the lithium nosocomial slurry, and react with residual alkali through the silicane group to form a ultra -thin interface layer to reduce the effect of residual alkali. Base, slow down the side reaction.

Benefits of technology

Effectively removes residual alkali on the surface of the positive electrode lithium replenishing agent, prolongs battery life, improves dynamic performance, reduces interface impedance, and improves battery cycle life and rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118676375B_ABST
    Figure CN118676375B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of lithium batteries, and specifically provides a lithium-replenishing positive electrode slurry and a preparation method thereof, a positive electrode sheet, and a lithium-ion battery. It aims to solve the problem that the residual alkali on the surface of the existing positive electrode lithium replenisher is too high and affects the battery performance. To this end, the lithium-replenishing positive electrode slurry of the present application includes a positive electrode active substance, a solvent, a positive electrode lithium replenisher and an additive, wherein the additive includes a silane additive and a weak acid additive, the silane additive contains a silane group, and the weak acid additive is ascorbic acid and / or a carboxylic acid. The present application adds silane additives and weak acid additives to the lithium-replenishing positive electrode slurry, which can induce the formation of an ultra-thin interface layer on the surface of the positive electrode lithium replenisher to enhance the dynamics, and while removing the residual alkali on the surface of the positive electrode lithium replenisher, an alcohol substance is formed to remove free radicals, slow down the occurrence of side reactions, and extend the battery life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium batteries, and specifically provides a lithium-supplemented positive electrode slurry and a preparation method thereof, a positive electrode sheet, and a lithium-ion battery. Background Art

[0002] Lithium-ion batteries (LIBs) have the advantages of high energy density, high operating voltage, long cycle life, low self-discharge and no memory effect. They show great development prospects in the field of electrochemical energy storage. Their unique advantages have promoted the rapid development of photovoltaic energy storage with lithium-ion batteries as the main body. In order to match the long-life photovoltaic products, it is extremely important to significantly extend the cycle life of lithium-ion battery energy storage equipment. During the formation and cycle stages of the battery, a solid electrolyte interface (SEI) will form on the surface of the negative electrode. This process will irreversibly and continuously consume the active lithium of the positive electrode, resulting in problems such as poor cycle life. Therefore, pre-lithiation or the addition of lithium supplements is required to improve the cycle life.

[0003] Negative electrode lithium supplementation has great problems in mass production due to the high activity of metallic lithium and the difficulty of melting lithium powder. However, positive electrode lithium supplementation can be added directly during the slurry mixing process. It is simple to operate and does not require improvement of the existing battery system. Its simplicity, speed and low cost make its large-scale mass production more promising. However, the residual alkali on the surface of most positive electrode lithium supplements is too high, which will cause the hydroxyl groups in the slurry to react with the binder polyvinylidene fluoride to undergo nucleophilic reaction and lead to defluorination, causing polyvinylidene fluoride to degrade and generate water, which will cause the rubber to gel. In addition, the residual alkali on the surface of the positive electrode lithium supplement will also cause the positive electrode surface to passivate and hinder the diffusion of lithium ions, increase impedance and aggravate the polarization of the battery cell.

[0004] Accordingly, this field requires a new technical solution to solve the above technical problems. Summary of the invention

[0005] The present application aims to solve the above technical problem, that is, to solve the problem that the residual alkali on the surface of the existing positive electrode lithium supplement is too high and affects the battery performance.

[0006] In a first aspect, the present application provides a lithium-replenishing positive electrode slurry, which includes a positive electrode active material, a solvent, a positive electrode lithium replenishing agent and an additive, wherein the additive includes a silane additive and a weak acid additive, the silane additive contains a silane group, and the weak acid additive is ascorbic acid and / or carboxylic acid.

[0007] In the preferred technical solution of the above-mentioned lithium-supplemented positive electrode slurry, the positive electrode active substance includes a positive electrode active material, a conductive agent and a binder, and the added amount of the additive is 0.8wt%~10wt% of the positive electrode active material.

[0008] In the preferred technical solution of the above-mentioned lithium-supplemented positive electrode slurry, the molar ratio of the silane additive to the weak acid additive is (0.5~2):1.

[0009] In the preferred technical scheme of the above-mentioned lithium-supplemented positive electrode slurry, the silane additive includes at least one of epoxy silane, vinyl trimethoxy silane, bisamino silane, and aminopropyl dimethoxymethyl silane; and / or, the carboxylic acid includes at least one of citric acid, oxalic acid, benzoic acid, and salicylic acid.

[0010] In the preferred technical solution of the above-mentioned lithium-supplemented positive electrode slurry, the positive electrode lithium supplement agent includes at least one of lithium-rich lithium nickel oxide, lithium-rich lithium iron oxide, lithium-rich lithium oxalate, lithium-rich lithium manganese oxide, and lithium-rich lithium cobalt oxide.

[0011] In the preferred technical solution of the above-mentioned lithium-supplemented positive electrode slurry, the positive electrode active material includes the following components by weight percentage: 90% to 97% of positive electrode active material, 1% to 5% of conductive agent, and 2% to 5% of binder.

[0012] In the preferred technical scheme of the above-mentioned lithium-supplemented positive electrode slurry, the positive electrode active material includes at least one of lithium iron phosphate, lithium cobalt oxide, and lithium nickel cobalt manganese oxide; and / or the conductive agent includes at least one of conductive carbon black, acetylene black, Ketjen black, carbon nanofiber tubes, carbon nanotubes, and graphene; and / or the binder includes at least one of fluorine-containing resin, polypropylene resin, polyacrylic acid, modified polyacrylic acid, polyaniline, polyimide, and rubber-based binders.

[0013] In a second aspect, the present application provides a method for preparing a lithium-replenishing positive electrode slurry, the preparation method comprising the following steps: dissolving the silane additive in the solvent to obtain a first additive solution; adding the positive electrode lithium replenisher and the positive electrode active material to the first additive solution, stirring evenly to obtain a first slurry; dissolving the weak acid additive in the solvent to obtain a second additive solution; adding the second additive solution to the first slurry, and then adding a binder and a conductive agent in sequence, stirring evenly to obtain the lithium-replenishing positive electrode slurry.

[0014] In a third aspect, the present application provides a positive electrode sheet, comprising: a positive electrode current collector; and the above-mentioned lithium-supplementing positive electrode slurry coated on the surface of the positive electrode current collector as a positive electrode film.

[0015] In a fourth aspect, the present application provides a lithium-ion battery, wherein the lithium-ion battery comprises the above-mentioned positive electrode sheet.

[0016] Compared with the prior art, the lithium-supplemented positive electrode slurry of the present application has the following beneficial effects:

[0017] (1) Adding silane additives and weak acid additives to the lithium replenishing positive electrode slurry, wherein the silane group of the silane additive can react with the hydroxyl group of the residual alkali on the surface of the positive electrode lithium replenisher, and then the weak acid additive is precisely deposited through acid-base interaction, thereby inducing the formation of an ultra-thin interface layer on the surface of the positive electrode lithium replenisher to enhance the kinetics, and while removing the residual alkali on the surface of the positive electrode lithium replenisher, alcohol substances are formed to remove free radicals, slow down the occurrence of side reactions, and extend the battery life;

[0018] (2) In the process of preparing the lithium-replenishing positive electrode slurry, a silane additive is first introduced to allow the hydroxyl groups in the residual alkali to guide the silane groups to react, so that the silane additive is deposited at the residual alkali without consuming the reaction sites of the active substance. Then, a weak acid additive is introduced to precisely anchor the weak acid additive through acid-base interaction, thereby inducing the formation of an ultra-thin and uniform interface layer on the surface of the positive electrode lithium replenisher to enhance the kinetics, reduce the interface impedance, and improve the battery cycle life and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The preferred embodiments of the present application are described below in conjunction with the accompanying drawings, in which:

[0020] Figure 1 is a 60° C. cycle performance graph of the batteries of Examples 1 to 6 of the present application and the comparative example when the capacity retention rate is reduced to 85%;

[0021] Figure 2 It is the impedance spectrum of the battery of Examples 1-6 and the comparative example of the present application;

[0022] Figure 3 This is a transmission electron microscope image of the positive electrode lithium replenishing agent in the lithium replenishing positive electrode slurry in Example 6 of the present application. DETAILED DESCRIPTION

[0023] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0024] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0025] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0026] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0027] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0028] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0029] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0030] The experimental methods in the following examples are conventional methods unless otherwise specified, and the materials, reagents, etc. used in the following examples are commercially available unless otherwise specified.

[0031] The invention aims to solve the problem that the residual alkali content of the positive electrode lithium supplement in the prior art is high and affects the battery performance.

[0032] The present application provides a lithium-replenishing positive electrode slurry, to which a silane additive and a weak acid additive are added, wherein the silaneoxy group in the silane group of the silane additive can react with the hydroxyl group of the residual alkali on the surface of the positive electrode lithium replenisher, and then the weak acid additive is precisely deposited through acid-base interaction, which can induce the formation of an ultra-thin interface layer on the surface of the positive electrode lithium replenisher to enhance the kinetics, thereby forming an alcohol substance while removing the residual alkali on the surface of the positive electrode lithium replenisher to remove free radicals, slow down the occurrence of side reactions, and extend the battery life.

[0033] Specifically, the present application provides a lithium-replenishing positive electrode slurry in a first aspect, which includes a positive electrode active material, a solvent, a positive electrode lithium replenishing agent and an additive, wherein the additive includes a silane additive and a weak acid additive, the silane additive contains a silane group, and the weak acid additive is ascorbic acid and / or carboxylic acid.

[0034] The lithium-replenishing positive electrode slurry of the present application adds silane additives and weak acid additives, so that the silane group in the silane group in the silane additive can react with the hydroxyl group of the residual base on the surface of the positive electrode lithium replenisher (Si-OR + LiOH →Si-O-Li + HO-R, wherein Si-OR represents the silane group, LiOH represents the residual base, Si-O-Li represents the product after the reaction, and HO-R represents the leaving group), and then the weak acid additive is precisely deposited through the acid-base interaction (specifically, the weak acid additive can combine with the free group in the silane additive and the generated alcohol substance), thereby inducing the formation of an ultra-thin interface layer on the positive electrode surface to enhance the kinetics, thereby removing the residual base on the surface of the positive electrode lithium replenisher while forming alcohol substances, and scavenging free radicals, slowing down the occurrence of side reactions, and extending the battery life.

[0035] In some embodiments, the positive electrode active material includes a positive electrode active material, a conductive agent, and a binder, and the additive is added in an amount of 0.8 wt % to 10 wt % of the positive electrode active material.

[0036] Specifically, the additive may be added in an amount of 0.8 wt %, 1.2 wt %, 2 wt %, 3 wt %, 4 wt %, 5 wt %, 6 wt %, 8 wt % or 10 wt % of the positive electrode active material.

[0037] In a preferred embodiment, the additive is added in an amount of 0.8 wt % of the positive electrode active material.

[0038] By controlling the total amount of additives added relative to the positive electrode active material, the uniformity of the ultra-thin interface layer formed on the positive electrode surface can be regulated, thereby improving the degree of removal of residual alkali, enhancing battery performance, and better extending battery life.

[0039] In some embodiments, the molar ratio of the silane additive to the weak acid additive is (0.5-2):1.

[0040] Specifically, the molar ratio of the silane additive to the weak acid additive may be 0.5:1 (ie, 1:2), 1:1, 1.5:1 (ie, 3:2), or 2:1.

[0041] In a preferred embodiment, the molar ratio of the silane additive to the weak acid additive is 2:1.

[0042] By adjusting the addition ratio of silane additives and weak acid additives, the interaction effect between silane additives and weak acid additives can be better controlled to better improve battery performance.

[0043] It should be noted that the present application does not impose any restrictions on the specific substances of the silane additive. As long as the silane additive contains silane groups and can react with the hydroxyl groups of the residual alkali on the surface of the positive electrode lithium replenisher to remove the residual alkali, in practical applications, those skilled in the art can select the specific components of the silane additive according to actual needs.

[0044] Optionally, the silane additive includes at least one of epoxy silane, vinyl trimethoxy silane, bisamino silane, and aminopropyl dimethoxymethyl silane.

[0045] In a preferred embodiment, the silane additive is aminopropyldimethoxymethylsilane.

[0046] In practical applications, aminopropyldimethoxymethylsilane is selected as the silane additive, and good effects are achieved, especially when combined with ascorbic acid.

[0047] It should be noted that the present application does not impose any restrictions on the specific substances of the weak acid additives, as long as the weak acid additives are ascorbic acid and / or carboxylic acid. In practical applications, technicians in this field can select the specific components of the weak acid additives according to actual needs.

[0048] Optionally, the carboxylic acid includes at least one of ascorbic acid, citric acid, oxalic acid, benzoic acid, and salicylic acid.

[0049] In a preferred embodiment, the weak acid additive is ascorbic acid.

[0050] In practical applications, ascorbic acid is selected as the weak acid additive, and good effects are achieved, especially when combined with aminopropyldimethoxymethylsilane.

[0051] Optionally, the positive electrode lithium supplement includes lithium-rich nickel oxide (Li 2 NiO 2 )、LiFePO4(Li 5 FeO4 )、Li-rich lithium oxalate (Li 2 C 2 O 4 ), lithium-rich lithium manganese oxide (Li 2 MnO 3 , Li 6 MnO 4 )、Li-rich cobalt oxide (Li 6 CoO 4 ) at least one of the following.

[0052] In some preferred embodiments, the positive electrode active material includes the following components in terms of weight percentage: 90% to 97% of positive electrode active material, 1% to 5% of conductive agent, and 2% to 5% of binder.

[0053] Optionally, the positive electrode active material includes at least one of lithium iron phosphate, lithium cobalt oxide, and lithium nickel cobalt manganese oxide.

[0054] Optionally, the conductive agent includes at least one of conductive carbon black, acetylene black, Ketjen black, carbon nanofiber tubes, carbon nanotubes, and graphene.

[0055] Optionally, the adhesive includes at least one of fluorine-containing resin, polypropylene resin, polyacrylic acid, modified polyacrylic acid, polyaniline, polyimide, and rubber adhesive.

[0056] In a second aspect, the present application provides a method for preparing a lithium-supplemented positive electrode slurry. The method for preparing a lithium-supplemented positive electrode slurry specifically comprises the following steps:

[0057] S1: dissolving the silane additive in a solvent to obtain a first additive solution;

[0058] S2: adding the positive electrode lithium supplement and the positive electrode active material to the first additive solution, stirring evenly, to obtain a first slurry;

[0059] S3: dissolving a weak acid additive in a solvent to obtain a second additive solution;

[0060] S4: adding the second additive solution to the first slurry, and then sequentially adding a binder and a conductive agent, stirring evenly to obtain a lithium-supplemented positive electrode slurry.

[0061] The preparation method of the lithium-replenishing positive electrode slurry of the present application is to uniformly mix the first additive solution with the positive electrode lithium replenisher and the positive electrode active material in step S2 to obtain a first slurry, so that the silane group in the silane additive reacts with the hydroxyl group of the residual base on the surface of the positive electrode lithium replenisher, which is selective and avoids consuming active sites. The specific reaction is as follows: Si-OR + LiOH→ Si-O-Li + HO-R, wherein Si-OR represents silaneoxy, LiOH represents residual base, Si-O-Li represents the product after the reaction, and HO-R represents the leaving group; then in step S3, a weak acid additive is introduced to perform an acid-base reaction to guide the weak acid additive to be precisely deposited on the surface of the positive electrode lithium replenisher containing the silane group, specifically, the weak acid additive can combine with the free group in the silane additive and the generated alcohol substance, thereby inducing the formation of an ultra-thin interface layer on the surface of the positive electrode lithium replenisher.

[0062] The present application further provides a positive electrode sheet in a third aspect. The positive electrode sheet includes a positive electrode collector and a positive electrode film. The positive electrode film is prepared by coating the above-mentioned lithium-supplementing positive electrode slurry on the surface of the positive electrode collector.

[0063] In one embodiment, the positive electrode current collector is aluminum foil.

[0064] The present application further provides a lithium-ion battery in a fourth aspect, the lithium-ion battery comprising a negative electrode sheet, a separator, an electrolyte and the positive electrode sheet provided in the third aspect above.

[0065] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode film located on the surface of the negative electrode current collector, wherein the negative electrode film is prepared by coating a negative electrode slurry on the surface of the negative electrode current collector.

[0066] In some embodiments, the negative electrode slurry includes a negative electrode active material, a negative electrode solvent, and a negative electrode additive.

[0067] In some embodiments, the negative electrode active material includes a negative electrode active material, a negative electrode conductor, and a negative electrode binder.

[0068] In some embodiments, the negative electrode slurry includes the following components by weight: 90% to 97% of negative electrode active material, 1% to 5% of negative electrode conductive agent, and 2% to 5% of negative electrode binder.

[0069] Optionally, the negative electrode active material includes at least one of artificial graphite, natural graphite, and composite graphite.

[0070] Optionally, the negative electrode conductive agent includes at least one of conductive carbon black, acetylene black, Ketjen black, carbon nanofiber tubes, carbon nanotubes, and graphene.

[0071] Optionally, the negative electrode binder includes at least one of fluorine-containing resin, polypropylene resin, polyacrylic acid, modified polyacrylic acid, polyaniline, polyimide, and rubber-based binders.

[0072] In some embodiments, the isolation membrane is a porous sheet or layered membrane made of polyethylene, polypropylene or non-woven fabric, and its surface is coated with ceramic material, boehmite, silica, barium sulfate, polyvinylidene fluoride, polymethyl methacrylate, polyacrylonitrile and aramid, etc.

[0073] In some embodiments, the electrolyte includes an organic solvent and a lithium salt, wherein the organic solvent includes at least one of a carbonate, carboxylate, ether or ketone solvent, and the lithium salt includes LiPF 6 , LiFSI, LiTFSI, LiBOB, LiBF 4 、LiPF 6 、LiCF 3 SO 3 、LiCF 3 CO 2 、LiAsF 6 、LiSbF 6 、LiAlCl 4 、LiPO 2 F 2 , Li 2 PO 3 F, LiAsF 6 At least one of .

[0074] The technical solution of the present application is described in detail below through several specific embodiments of lithium-ion batteries.

[0075] The negative electrode sheets in the examples and comparative examples of the present application are prepared by the following steps:

[0076] (1) 96% active material, 2% conductive carbon black, 1.2% sodium carboxymethyl cellulose and 0.8% styrene-butadiene rubber are uniformly dispersed in water to form a negative electrode slurry;

[0077] (2) coating the negative electrode slurry on a 6 μm thick carbon-coated copper foil with a coating thickness of 150 μm;

[0078] (3) Dry in a vacuum drying oven at 60°C for 24 h and cut into 16 mm discs to obtain the negative electrode sheet to be used in the assembled battery.

[0079] The isolation membranes in the examples and comparative examples of the present application are prepared by the following steps: ceramic (3 μm) and PVDF glue (2 μm) are coated on the surface of a porous polymer membrane (9 μm) of polyethylene to obtain an isolation membrane.

[0080] The lithium-ion batteries in the embodiments and comparative examples of the present application are assembled by the following steps: assembling the positive electrode sheet, the negative electrode sheet, and the isolation membrane and injecting the electrolyte to form a 2032 button battery, wherein the electrolyte in the button battery is 1 mol / L LiFSI dissolved in EC / DEC (3:1), and the amount of electrolyte added is 80 μL.

[0081] Example 1

[0082] The positive electrode sheet of this embodiment is prepared by the following steps:

[0083] 25.6 mg of vinyltrimethoxysilane was dissolved in 1.505 g of NMP (N-methylpyrrolidone), followed by stirring for 30 min to obtain a first additive solution.

[0084] 610 mg of lithium iron phosphate and 12.2 mg of lithium-rich nickel oxide were added to the first additive solution, stirred and reacted for 2 h to obtain a first slurry.

[0085] 35.4 mg of ascorbic acid (containing organic acid) was dissolved in 20 ml of NMP and stirred for 2 h to fully dissolve to obtain a second additive solution.

[0086] The second additive solution was added to the first slurry, and then 76.25 mg of PVDF (polyvinylidene fluoride) was slowly added and stirred for 30 min. Finally, 76.25 mg of Super P (conductive agent, small particle conductive carbon black) was added and stirred for 6 h to obtain a lithium-supplemented positive electrode slurry.

[0087] The slurry was evenly coated on aluminum foil with a coating thickness of 150 μm, dried in a vacuum oven at 60 °C for 48 h, and cut into 16 mm discs to obtain the positive electrode sheet to be used in the assembled battery.

[0088] Example 2

[0089] The positive electrode sheet of this embodiment is prepared by the following steps:

[0090] 32.6 mg of aminopropyldimethoxymethylsilane was dissolved in 1.73 g of NMP, followed by stirring for 30 min to obtain a first additive solution.

[0091] 710 mg of lithium iron phosphate and 14.0 mg of lithium-rich nickel oxide were added to the first additive solution, and after stirring and reacting for 2 h, a first slurry was obtained.

[0092] Dissolve 38.4 mg of citric acid in 20 ml of NMP and stir for 2 h to fully dissolve to obtain a second additive solution.

[0093] The second additive solution was added to the first slurry, and then 87.5 mg of PVDF was slowly added and stirred for 30 min. Finally, 87.5 mg of Super P was added and stirred for 6 h to obtain a lithium-supplemented positive electrode slurry.

[0094] The slurry was evenly coated on aluminum foil with a coating thickness of 150 μm, dried in a vacuum oven at 60 °C for 48 h, and cut into 16 mm discs to obtain the positive electrode sheet to be used in the assembled battery.

[0095] Example 3

[0096] The positive electrode sheet of this embodiment is prepared by the following steps:

[0097] 32.6 mg of aminopropyldimethoxymethylsilane was dissolved in 1.68 g of NMP, followed by stirring for 30 min to obtain a first additive solution.

[0098] 680 mg of lithium iron phosphate and 13.6 mg of lithium-rich nickel oxide were added to the first additive solution, and after stirring and reacting for 2 h, a first slurry was obtained.

[0099] 35.4 mg of ascorbic acid was dissolved in 20 ml of NMP and stirred for 2 h to fully dissolve to obtain a second additive solution.

[0100] The second additive solution was added to the first slurry, and then 85 mg of PVDF was slowly added and stirred for 30 min. Finally, 85 mg of Super P was added and stirred for 6 h to obtain a lithium-supplemented positive electrode slurry.

[0101] The slurry was evenly coated on aluminum foil with a coating thickness of 150 μm, dried in a vacuum oven at 60 °C for 48 h, and cut into 16 mm discs to obtain the positive electrode sheet to be used in the assembled battery.

[0102] Example 4

[0103] The positive electrode sheet of this embodiment is prepared by the following steps:

[0104] 32.6 mg of aminopropyldimethoxymethylsilane was dissolved in 5.128 g of NMP, followed by stirring for 30 min to obtain a first additive solution.

[0105] 2060 mg of lithium iron phosphate and 41.2 mg of lithium-rich lithium ferrite were added to the first additive solution, and after stirring and reacting for 2 h, a first slurry was obtained.

[0106] 70.4 mg of ascorbic acid was dissolved in 20 ml of NMP and stirred for 2 h to fully dissolve to obtain a second additive solution.

[0107] The second additive solution was added to the first slurry, and then 257.5 mg of PVDF was slowly added and stirred for 30 min. Finally, 257.5 mg of Super P was added and stirred for 6 h to obtain a lithium-supplemented positive electrode slurry.

[0108] The slurry was evenly coated on aluminum foil with a coating thickness of 150 μm, dried in a vacuum oven at 60 °C for 48 h, and cut into 16 mm discs to obtain the positive electrode sheet to be used in the assembled battery.

[0109] Example 5

[0110] The positive electrode sheet of this embodiment is prepared by the following steps:

[0111] 65.2 mg of aminopropyldimethoxymethylsilane was dissolved in 5.01 g of NMP, followed by stirring for 30 min to obtain a first additive solution.

[0112] 2012 mg of lithium iron phosphate and 40.24 mg of lithium-rich lithium ferrite were added to the first additive solution, and after stirring and reacting for 2 h, a first slurry was obtained.

[0113] 35.4 mg of ascorbic acid was dissolved in 20 ml of NMP and stirred for 2 h to fully dissolve to obtain a second additive solution.

[0114] The second additive solution was added to the first slurry, and then 251.5 mg of PVDF was slowly added and stirred for 30 min. Finally, 251.5 mg of Super P was added and stirred for 6 h to obtain a lithium-supplemented positive electrode slurry.

[0115] The slurry was evenly coated on aluminum foil with a coating thickness of 150 μm, dried in a vacuum oven at 60 °C for 48 h, and cut into 16 mm discs to obtain the positive electrode sheet to be used in the assembled battery.

[0116] Example 6

[0117] The positive electrode sheet of this embodiment is prepared by the following steps:

[0118] 65.2 mg of aminopropyldimethoxymethylsilane was dissolved in 31.44 g of NMP, followed by stirring for 30 min to obtain a first additive solution.

[0119] 12.575 g of lithium iron phosphate and 2.515 g of lithium-rich lithium ferrite were added to the first additive solution, and stirred and reacted for 2 h to obtain a first slurry.

[0120] 35.4 mg of ascorbic acid was dissolved in 20 ml of NMP and stirred for 2 h to fully dissolve to obtain a second additive solution.

[0121] The second additive solution was added to the first slurry, and then 1.572 g of PVDF was slowly added and stirred for 30 min. Finally, 1.572 g of Super P was added and stirred for 6 h to obtain a lithium-supplemented positive electrode slurry.

[0122] The slurry was evenly coated on aluminum foil with a coating thickness of 150 μm, dried in a vacuum oven at 60 °C for 48 h, and cut into 16 mm discs to obtain the positive electrode sheet to be used in the assembled battery.

[0123] The lithium supplemented positive electrode slurry prepared in this embodiment was observed by transmission electron microscopy, and the following Figure 3 The electron microscope scanning image of the positive electrode lithium supplement is shown.

[0124] Example 7

[0125] The positive electrode sheet of this embodiment is prepared by the following steps:

[0126] 40.62 mg of aminopropyldimethoxymethylsilane was dissolved in 1.73 g of NMP, followed by stirring for 30 min to obtain a first additive solution.

[0127] 710 mg of lithium iron phosphate and 14.0 mg of lithium-rich nickel oxide were added to the first additive solution, and after stirring and reacting for 2 h, a first slurry was obtained.

[0128] Dissolve 30.38 mg of benzoic acid in 20 ml of NMP and stir for 2 h to fully dissolve to obtain a second additive solution.

[0129] The second additive solution was added to the first slurry, and then 87.5 mg of PVDF was slowly added and stirred for 30 min. Finally, 87.5 mg of Super P was added and stirred for 6 h to obtain a lithium-supplemented positive electrode slurry.

[0130] The slurry was evenly coated on aluminum foil with a coating thickness of 150 μm, dried in a vacuum oven at 60 °C for 48 h, and cut into 16 mm discs to obtain the positive electrode sheet to be used in the assembled battery.

[0131] Example 8

[0132] The positive electrode sheet of this embodiment is prepared by the following steps:

[0133] 38.42 mg of aminopropyldimethoxymethylsilane was dissolved in 1.73 g of NMP, followed by stirring for 30 min to obtain a first additive solution.

[0134] 710 mg of lithium iron phosphate and 14.0 mg of lithium-rich nickel oxide were added to the first additive solution, and after stirring and reacting for 2 h, a first slurry was obtained.

[0135] 32.54 mg of salicylic acid was dissolved in 20 ml of NMP and stirred for 2 h to fully dissolve to obtain a second additive solution.

[0136] The second additive solution was added to the first slurry, and then 87.5 mg of PVDF was slowly added and stirred for 30 min. Finally, 87.5 mg of Super P was added and stirred for 6 h to obtain a lithium-supplemented positive electrode slurry.

[0137] The slurry was evenly coated on aluminum foil with a coating thickness of 150 μm, dried in a vacuum oven at 60 °C for 48 h, and cut into 16 mm discs to obtain the positive electrode sheet to be used in the assembled battery.

[0138] Comparative Example

[0139] The positive electrode sheet of this comparative example is prepared by the following steps:

[0140] 610 mg of lithium iron phosphate and 12.2 mg of lithium-rich lithium ferrite were dissolved in 1.525 g of NMP and stirred for 2 h to obtain a first slurry.

[0141] Slowly add 76.25 mg of PVDF to the first slurry and stir for 30 min, and finally add 76.25 mg of Super P. After stirring for 6 h, a lithium-supplemented positive electrode slurry is obtained.

[0142] The slurry was evenly coated on aluminum foil with a coating thickness of 150 μm, dried in a vacuum oven at 60 °C for 48 h, and cut into 16 mm discs to obtain the positive electrode sheet to be used in the assembled battery.

[0143] The pH value and residual lithium concentration of the lithium-supplemented positive electrode slurry prepared in the embodiment and the comparative example were tested, and the test results are shown in Table 1.

[0144] The batteries prepared in the embodiment and the comparative example were subjected to cycle tests in a 60°C constant temperature box to test the cycle life and impedance performance of the batteries when the capacity retention rate was 85%. The test data are shown in Table 1, and the following are obtained: Figure 1The 60°C cycle performance diagram when the capacity retention rate is reduced to 85% is shown in the figure and Figure 2 Impedance spectrum shown.

[0145] Table 1 Test data of embodiments and comparative examples

[0146]

[0147] Combine the experimental data in Table 1 with the Figure 1 To Attachment Figure 3 To perform the analysis:

[0148] 1. Comparing the pH values ​​of the lithium-replenishing positive electrode slurries of Examples 1 to 8 with those of the comparative example, the pH value of the comparative example is significantly higher than that of Examples 1 to 8. It can be seen that the pH value of the slurry in the battery of the comparative example can be significantly reduced by simultaneously adding silane additives and weak acid additives to the lithium-replenishing positive electrode slurry, so that the lithium-replenishing positive electrode slurry of the present application can effectively remove the residual alkali on the surface of the positive electrode lithium replenisher by adding silane additives and weak acid additives.

[0149] 2. The pH values ​​of the lithium-supplemented positive electrode slurries of Examples 1 to 8 were compared with those of the comparative example, wherein the amount of the additive added in Examples 1 to 3 and Examples 7 to 8 was 10 wt % and the silane additive and the weak acid additive were mixed in a molar ratio of 1:1, the amount of the additive added in Example 4 was 5 wt % and the silane additive and the weak acid additive were mixed in a molar ratio of 1:2, the amount of the additive added in Example 5 was 5 wt % and the silane additive and the weak acid additive were mixed in a molar ratio of 2:1, and the amount of the additive added in Example 6 was 0.8 wt % and the silane additive and the weak acid additive were mixed in a molar ratio of 2:1. Specifically, compared to the pH value of 12.92 in the comparative example, the pH values ​​in Examples 1 to 3 and Examples 7 to 8 can all be reduced to about 12, the pH value of Example 4 is slightly higher than that of Example 3, the pH value of Example 5 is lower than that of Examples 1 to 4, and the pH value of Example 6 is lower than that of Example 5. It can be seen that increasing the molar ratio of the silane additive to the weak acid additive while reducing the amount of the additive added can further reduce the pH value of the slurry (i.e., improve the removal efficiency of the residual alkali). Therefore, it is preferred that the amount of the additive added is 0.8wt% of the positive electrode active material, and the molar ratio of the silane additive to the weak acid additive is preferably 2:1.

[0150] In addition, the pH value of Example 3 is lower than that of Example 1 and Example 2, which shows that, under the same additive amount and molar ratio, when the silane additive is aminopropyl dimethoxymethyl silane and the weak acid additive is ascorbic acid, the effect of removing residual alkali is better. Therefore, preferably, the silane additive is aminopropyl dimethoxymethyl silane and the weak acid additive is ascorbic acid.

[0151] 3. Comparing the residual lithium content in the slurry of Examples 1 to 8 with that of the comparative example, by increasing the molar ratio of the silane additive and the weak acid additive while reducing the amount of additive added, the residual lithium content will be further reduced, and the residual lithium content is reduced from 1.425 wt% in the comparative example to 0.444 wt% in the optimal example 6. Therefore, the lithium-supplemented positive electrode slurry of the present application can inhibit the consumption of active lithium and slow down the occurrence of side reactions by adding silane additives and weak acid additives.

[0152] 4. Combine with attachment Figure 2 Comparing the impedance values ​​of the batteries of Examples 1 to 8 and the comparative example, the impedance values ​​were significantly reduced by increasing the molar ratio of the silane additive to the weak acid additive and reducing the amount of the additive added. It can be seen that the lithium-supplemented positive electrode slurry of the present application can effectively improve the battery performance during use.

[0153] 5. Compare the cycle life of the batteries of Examples 1 to 8 with that of the comparative example and combine Figure 1 It can be seen that, at 60°C and a rate of 2C, the capacity retention rate of the comparative example is reduced to 85% after only 113 cycles, the capacity retention rate of Example 1 is reduced to 85% after 846 cycles, the capacity retention rate of Example 2 is reduced to 85% after 860 cycles, the capacity retention rate of Example 3 is reduced to 85% after 970 cycles, the capacity retention rate of Example 4 is reduced to 85% after 960 cycles, the capacity retention rate of Example 5 is reduced to 85% after 904 cycles, and the capacity retention rate of Example 6 is reduced to 85% after 1027 cycles, the capacity retention rate of Example 7 is reduced to 85% after 853 cycles, and the capacity retention rate of Example 8 is reduced to 85% after 915 cycles; it can be seen that the lithium supplemented positive electrode slurry of the present application can effectively extend the cycle life of the battery when used in the battery, among which the cycle life of the battery corresponding to Example 6 is the longest, so it is preferred that the amount of additive added is 0.8 wt% of the positive electrode active material, and the molar ratio of the silane additive to the weak acid additive is 2:1.

[0154] In addition, a transmission electron microscope was used to observe that a thin and uniform interface layer of about 2 to 3 nm was formed on the surface of the positive electrode lithium supplement agent in Example 6 (the electron microscope scanning image of the positive electrode lithium supplement agent is shown in FIG. Figure 3 As shown), it can be seen that the lithium-supplemented positive electrode slurry of the present application can induce the formation of an ultra-thin and uniform interface layer on the surface of the positive electrode lithium-supplementing agent, thereby enhancing the kinetics, reducing the interface impedance, and improving the battery cycle life and rate performance.

[0155] In summary, the novel slurry additive method for removing residual alkali on the surface of the positive electrode lithium replenisher invented in the present application can accurately control the residual alkali on the surface of the positive electrode lithium replenisher by changing the amount of additive added, the type and molar ratio of the silane additive and the weak acid additive, without consuming more active sites, thereby forming an ultra-thin interface layer on the surface of the positive electrode lithium replenisher to enhance the kinetics, inhibit the consumption of active lithium, slow down the occurrence of side reactions, and thus extend the high-temperature cycle life of the battery.

[0156] So far, the technical solutions of the present application have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present application is obviously not limited to these specific embodiments. Without departing from the principles of the present application, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present application.

Claims

1. A lithium-supplemented positive electrode slurry, characterized in that: The lithium-supplemented positive electrode slurry comprises a positive electrode active material, a solvent, a positive electrode lithium-supplementing agent and an additive, wherein the additive comprises a silane additive and a weak acid additive, the silane additive contains a silane group, and the weak acid additive is ascorbic acid and / or carboxylic acid; The positive electrode lithium supplement comprises at least one of lithium-rich nickel oxide, lithium-rich iron oxide, lithium-rich lithium oxalate, lithium-rich lithium manganese oxide, and lithium-rich lithium cobalt oxide; The positive electrode active material comprises a positive electrode active material, a conductive agent and a binder, and the positive electrode active material is lithium iron phosphate; The lithium supplemented positive electrode slurry is prepared by the following steps: dissolving the silane additive in the solvent to obtain a first additive solution; Adding the positive electrode lithium supplement and the positive electrode active material into the first additive solution, stirring evenly, to obtain a first slurry; dissolving the weak acid additive in the solvent to obtain a second additive solution; The second additive solution is added to the first slurry, and then a binder and a conductive agent are added in sequence, and stirred evenly to obtain the lithium-supplemented positive electrode slurry.

2. The lithium supplemented positive electrode slurry according to claim 1, characterized in that: The additive is added in an amount of 0.8 wt % to 10 wt % of the positive electrode active material.

3. The lithium supplemented positive electrode slurry according to claim 1, characterized in that: The molar ratio of the silane additive to the weak acid additive is (0.5-2):

1.

4. The lithium-supplemented positive electrode slurry according to any one of claims 1 to 3, characterized in that: The silane additive includes at least one of epoxy silane, vinyl trimethoxy silane, bisamino silane, and aminopropyl dimethoxymethyl silane; And / or, the carboxylic acid includes at least one of citric acid, oxalic acid, benzoic acid, and salicylic acid.

5. The lithium supplemented positive electrode slurry according to claim 2, characterized in that: The positive electrode active material comprises the following components by weight percentage: 90% to 97% of positive electrode active material, 1% to 5% of conductive agent, and 2% to 5% of binder.

6. The lithium supplemented positive electrode slurry according to claim 2, characterized in that: The conductive agent includes at least one of conductive carbon black, acetylene black, Ketjen black, carbon nanofiber tube, carbon nanotube, and graphene; And / or, the binder includes at least one of fluorine-containing resin, polypropylene resin, polyacrylic acid, modified polyacrylic acid, polyaniline, polyimide, and rubber-based binders.

7. A method for preparing a lithium-supplemented positive electrode slurry, used for preparing the lithium-supplemented positive electrode slurry according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: dissolving the silane additive in the solvent to obtain a first additive solution; Adding the positive electrode lithium supplement and the positive electrode active material into the first additive solution, stirring evenly, to obtain a first slurry; dissolving the weak acid additive in the solvent to obtain a second additive solution; The second additive solution is added to the first slurry, and then a binder and a conductive agent are added in sequence, and stirred evenly to obtain the lithium-supplemented positive electrode slurry.

8. A positive electrode sheet, characterized in that: include: Positive electrode current collector; The lithium-supplemented positive electrode slurry according to any one of claims 1 to 6 is coated on the surface of the positive electrode current collector as a positive electrode film.

9. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet according to claim 8.

Citation Information

Patent Citations

  • Positive electrode lithium supplementing material, positive electrode plate containing positive electrode lithium supplementing material and electrochemical device

    CN114097111A